Eficácia do tratamento baseado em grupo versus cuidados usuais na melhora da dor e incapacidade de pacientes com dor lombar crônica inespecífica: uma revisão sistemática com metanálise - Silva, Raionara Figueiredo da (Brasil, 2022)
Introduction: Chronic low back pain is the world's number one cause of disability and absence from work. In 2015, the prevalence of activity-limiting low back pain was 7.3%, referring to 540 million people affected. However, in Brazil, data from the 2013 National Health Survey reveal a prevalence of 18.5% of complaints related to chronic problems in the spine, in view of this, such limitations impair quality of life. The practice of the SUS professional uses services based on scientific evidence, which would be essential to improve the care of this chronic patient and prevent the progression of this disabling disease. Objective: This study aimed to carry out a systematic review on the effectiveness of group physical therapy treatment in patients with chronic low back pain in the short and long term. Methodology: Searches were made in the SciELO, PubMed and PEDro databases, from September 2020 to January 2021 in Advanced Search using the following keywords: "group based" AND "low back pain", "group-based program”, “group-based exercise”, “group-based physioteherapy” and “group-based physical therapy”. Results: A total of 223 articles were found, 92 in the PEDro database, 112 in PubMed and 19 in SciELO, of these 223 articles found, 214 articles were excluded because they did not follow the eligibility criteria and only 9 were included in the search. Conclusion: There was no significant difference in the choice of treatment, being in groups or in other types of interventions, will achieve similar and efficient results.